A imagem do Diabo na Igreja Universal do Reino de Deus como instrumento de marketing e do medo: um estudo a partir de postagens de exorcismos encontradas no YouTube - Paim, Ivana Soares (2017)
This research studies the image of the Devil, which is taken from the stages of the Universal Church of the Kingdom of God (UCKG) to the YouTube, according to the context of the communications that take place in the socialnetworks. The corpus of this work is made by an assemblage of scenes of exorcisms spreaded on YouTube, from 2010 through 2014, years of continuous expansion of this Church. This study aims to investigate the elements that build the representation of the Devil in the rituals of exorcism at the UCKG. These elements come from the Christian imaginary as well as from that of the Afro-Brazilian religions; they also come from the relations between the television and the religious practices, and consequently, from the marketing strategies developed by this Church. This research works with the hypothesis that the image of the Devil at the UCKG is an instrument of advertisement, part of the revival of the buzz marketing at the video sharing media and its use by religious institutions, in case, the UCKG. As an instrument of advertisement for this Church, the image of the Devil is represented in a fearful way and takes some characteristics of the Afro-Brazilian divinities by a hybridization process between these two religious imaginaries, conditioned to the UCKG’s movement of updating itself in search for recognition in a society that belongs to the web era. To develop this study, this research will consider the ideas of Hans Belting and Lúcia Santaella about the fields in which images can be classified into, as well as Gilbert Durand’s theories about the imaginary, that enable us to understand the building of images or representations as a product resulted from the interaction between an individual and his culture. It will also consider the concept of provoqued event by Patrick Charaudeau, who thinks the mediatic image is a programmed and an expected construction, whose purpose is to “reveal a truth” by persuasion and emotional appeal with obvious advertising intentions. In addition, other references will be considered for this research, such as studies about religion and more specifically about some Afro-Brazilian religions, in order to make comparisons between representations of different divinities and that of the Christian Devil. It will also consider studies about the buzz marketing that consists of an advertising strategy that makes the clients advertise the product by motivating them to talk about it with friends and acquaintances. We believe that the importance of this work relies on its contribution for the studies around the religious marketing in the time of web communication, since religious institutions have taken profit from the convergent media like YouTube to update their strategies in search for visibility and more followers